Synthesis, characterisation and structure determination of 3-[(1Z)-{2-[bis({[(2-methylphenyl)methyl]sulfanyl})methylidene]hydrazin-1-ylidene}methyl]benzene-1,2-diol - Enis Nadia Md Yusof,; Tiekink, Edward R. T. *; Jotani, Mukesh M.; Simone, Michela I; Page, Alister J; Ravoof, Thahira Begum S. A. (Elsevier, 2018)
A light-yellow crystalline product (1), which was isolated after one week from the filtrate of the reaction between S-2-methylbenzyldithiocarbazate and 2,3-dihydroxybenzaldehyde, was characterised by single crystal X-ray diffraction, FTIR and NMR spectroscopic analyses. The experimental molecular structure of 1 has been established by X-ray crystallography and showed, to a first approximation, a planar C2N2S2 + dihydroxyphenyl region that has an almost orthogonal relationship to the rings of the pendant S-bound benzyl groups. This structure has been verified via density functional theory calculations using the B3LYP/6311G(d,p) level of theory. The molecular packing featured linear supramolecular chains along the b-axis sustained by tolyl-C–H…N(imine) and tolyl-C–H…π(tolyl) interactions; the importance of these contacts is indicated by a Hirshfeld surface analysis.